2023
DOI: 10.3390/jof9040401
|View full text |Cite
|
Sign up to set email alerts
|

Chestnut Brown Rot and Gnomoniopsis smithogilvyi: Characterization of the Causal Agent in Portugal

Abstract: Sweet chestnut (Castanea sativa Miller) is a nutritious food with high social and economic impacts in Portugal. The fungus Gnomoniopsis smithogilvyi (syn. Gnomoniopsis castaneae) is the causal agent of chestnut brown rot, and is currently considered one of the major threats to the chestnut production chain worldwide. Considering the lack of knowledge on both the disease and the causal agent in Portugal, studies were conducted in an attempt to develop the necessary control strategies towards the mitigation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…A phylogenetic tree of the TEF-α gene is shown in Figure S1 (supplementary material). G. smithogilvyi isolates obtained in this study showed a very close relation with the isolates retrieved from the GenBank, including the type strain, as previously shown [8].…”
Section: Identification Of Gnomoniopsis Smithogilvyi Isolatessupporting
confidence: 86%
See 3 more Smart Citations
“…A phylogenetic tree of the TEF-α gene is shown in Figure S1 (supplementary material). G. smithogilvyi isolates obtained in this study showed a very close relation with the isolates retrieved from the GenBank, including the type strain, as previously shown [8].…”
Section: Identification Of Gnomoniopsis Smithogilvyi Isolatessupporting
confidence: 86%
“…Several isolates of Gs obtained from these chestnuts were confirmed as the causal agent of chestnut brown rot and proved to be highly aggressive in chestnuts and well adapted to a wide range of temperatures, potentially resulting in extreme losses in the context of climatic changes [8].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Chestnut fruit provides favourable conditions for the invasion and reproduction of pathogens due to their high nutrient contents and strong respiratory intensity ( Possamai, Dallemole-Giaretta, Gomes-Laranjo, Sampaio, & Rodrigues, 2023 ). After being harvested, chestnuts remain viable seeds with a well-functioning defence enzyme and active oxygen-free radical clearance system.…”
Section: Introductionmentioning
confidence: 99%